Synthesis of zeolitic immidazolate framework membrane - Chua, Mei Ling. (2009)
Zeolitic Immidazolate Frameworks (ZIFs) are porous crystalline materials with structures having zeolite framework topologies, where inorganic transition metals such as zinc and cobalt are tetrahedrally coordinated with organic imidazolate links. They are thermally and chemically stable and the organic links offer design flexibility. The high selectivity and capacity for carbon dioxide make ZIFs promising candidates to reduce the amount of carbon dioxide emitted into the atmosphere. Synthesis of ZIF membranes, which was not yet reported in the literature, was explored in this study. ZIF-68, which has the zeolite topology of GME, is synthesized in this study and the synthesis methods, in-situ crystallization and seeded growth method, are adopted from the methodology used in synthesis of zeolite membranes. The membrane obtained by in-situ crystallization is continuous. Moreover, the crystals were randomly oriented and intergrowth between crystals on the porous alumina support can be clearly seen in the SEM images. Extra crystals were found to be adhering onto the walls of the Teflon container. Upon decreasing the concentration of the zinc ions in the solution, the obtained membrane was not continuous. Seeded growth technique was also experimented. The membrane obtained is continuous and thinner. Single-component gas permeation study on the membrane shows that the membrane has the same affinity for different gases due to its large pore size. Further optimization of the conditions and performing the gas separation tests are to be carried out as future works.